RETRACTED: Sediments of an underwater tunnel constructed by the immersed sections method - Shaposhnikov E.A.; Melnik I.V. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001